Factors That Influence the Risk of Chronic Energy Deficiency (CED) in Pregnant Women in the 2nd Tempo in The Working Area of The Jongkong Public Health Center, Kapuas Hulu Regency - Mastuti; Sulistiyah (CV. Publikasi Indonesia, 2026)
This study aims to explore the experiences and challenges faced by students during the Kuliah Kerja Nyata (KKN) regarding managing interpersonal communication to maintain relationships despite physical distance and differing schedules. This study used qualitative methods with a narrative approach. Data were collected through in-depth interviews. The results showed that students experienced a range of complex emotions, such as longing, sadness, anxiety, and frustration. These feelings mainly arise from disrupted communication routines, demanding KKN activities, and limited time for interaction. As a result, their communication patterns shift from emotionally oriented conversations to more functional interactions, primarily conducted through digital platforms such as WhatsApp using text messages and occasional video calls. To maintain relationships, students employ several strategies, including honesty, consistent communication, conflict management, commitment, and mutual understanding. Therefore, maintaining a long-distance relationship during the KKN period requires adaptive communication skills, effective emotional regulation, and an understanding of each partner's limitations. These findings highlight the importance of flexibility and emotional intelligence in maintaining relationships under challenging circumstances